Self-powered graphene-silicon photodetectors with hBN passivation - Low, Kelly Khe Li (Nanyang Technological University, 2024)
Photodetectors are emerging technologies used in telecommunications, optoelectronics, and sensing. Significant research has been conducted on improving the performance of Silicon (Si)- based optoelectronic devices such as photodetectors and solar cells. Typically, conventional photodetectors require an external voltage for operation, necessitating large packaging to accommodate the operating circuit. In contrast, Self-powered photodetector can operate without requiring an external energy source, offering significantly benefit emerging technologies like the Internet of Things (IoT), autonomous systems, and wearable devices. Therefore, the development of self-powered photodetector is crucial for reducing power consumption in devices, and it shows promise as a tool that can drive economic and technical growth and improve human lives